Metal free [4+1] and [5+1] annulation reactions to prepare heterocycles using DMF and its derivatives as one-carbon source. Issue 19 (7th May 2020) - Xu, Yiwen; Shen, Bei; Liu, Lingfeng; Qiao, Chunhua
Graphical abstract: Highlights: DMF as carbon source and solvent. Metal-free condition. High reaction yield. Broad substrate scope tolerated. Abstract: 1, 2, 4-Triazolo[3, 4- a ]pyridines and related heterocycles and substituted triazines were commonly discovered scaffolds in a variety of pharmaceutical and agrochemical agents. Herein, we report a highly efficient and practical method using DMF and its derivative for the [4+1] and [5+1] annulation reactions to prepare these heterocycles. This metal free reaction takes advantages of shelf stable DMF as solvent and carbon donor, imidazole chloride as a catalyst, the mild reaction condition tolerates a broad substrate range and substitutes. The prepared 3-unsubstituted 1, 2, 4-triazolo[3, 4- a ]pyridine and derivatives allow further introduction of a variety of functional group 1 at 3-position.